A book history study of Michael Radford's filmic production William Shakespeare's The Merchant of Venice - Green, Bryony Rose Humphries (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
Falling within the ambit of the Department of English Literature but with interdisciplinary scope and method, the research undertaken in this thesis examines Michael Radford's 2004 film production William Shakespeare's The Merchant of Venice using the Book History approach to textual study. Previously applied almost exclusively to the study of books, Book History examines the text in terms of both its medium and its content, bringing together bibliographical, literary and historical approaches to the study of books within one theoretical paradigm. My research extends this interdisciplinary approach into the filmic medium by using a modified version of Robert Darnton's "communication circuit" to examine the process of transmission of this Shakespearean film adaptation from creation to reception. The research is not intended as a complete Book History study and even less as a comprehensive investigation of William Shakespeare's The Merchant of Venice. Rather, it uses a Shakespearean case study to bring together the two previously discrete fields of Book History and filmic investigation. Drawing on film studies, literary concepts, cultural and media studies, modern management theory as well as reception theories and with the use of both quantitative and qualitative data, I show Book History to be an eminently useful and constructive approach to the study of film.
Keywords: Shakespeare, William, 1564-1616 -- Film adaptations; Shakespeare, William, 1564-1616 -- Merchant of Venice; Merchant of Venice (Motion picture: 2004); English drama -- Film and video adaptations; Film adaptations -- History and criticism